Approaching Tensions in Business Model Innovation for Sustainability: An Ordonomic Meta-Framework on Tensions - Schultz, Felix Carl (European Journal of Sustainable Development, 2022)
Business model innovation for sustainability (BMIfS) has recently seen a surge in academia and practice. This article introduces an ordonomic BMIfS meta-framework to further stimulate the growing research interest on how available approaches to tensions in BMIfS can be purposefully reconciled to improve the management of BMIfS. The ordonomic BMIfS meta-framework proposes an opportunity to mediate between the normative desiderata of integrative approaches and ‘practical’ instrumental ones to tensions, which feature prominently in the contemporary literature. Within this meta-framework, both approaches play equally important but categorially different roles. This article contributes by proposing to actively shape the ‘boundary conditions’ in BMIfS processes to prevent tensions manifesting in irreconcilable tradeoffs.